How is the reform of justice in Latin America going? Interview with Dr. Luis Pasara Pazos - Chumberiza Tupac Yupanqui, Mayté Pamela (2017)
The present interview indicate how the legal tradition inherited Latin America, from Spain and France, has been changing being as in the Latin tradition the judge’s role has been subordinated to political power, unlike other countries. Thus it is arises the motivations to start and continue, in many cases, with the reform of the justice system, where what is needed is a set of actors that define and carry out this reform.